Fatty acids and related lipid mediators in the regulation of cutaneous inflammation. (19th February 2018) - Kiezel-Tsugunova, Magdalena; Kendall, Alexandra C.; Nicolaou, Anna
Abstract : Human skin has a distinct profile of fatty acids and related bioactive lipid mediators that regulate many aspects of epidermal and dermal homeostasis, including immune and inflammatory reactions. Sebum lipids act as effective antimicrobial agents, shape immune cell communications and contribute to the epidermal lipidome. The essential fatty acid linoleic acid is crucial for the structure of the epidermal barrier, while polyunsaturated fatty acids act as precursors to eicosanoids, octadecanoids and docosanoids through cyclooxygenase, lipoxygenase and cytochrome P450 monooxygenase-mediated reactions, and endocannabinoids and N -acyl ethanolamines. Cross-communication between these families of bioactive lipids suggests that their cutaneous activities should be considered as part of a wider metabolic network that can be targeted to maintain skin health, control inflammation and improve skin pathologies.